1970
DOI: 10.1099/00221287-60-1-31
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Starvation on the Viability and Cellular Constituents of Zymomonas anaerobia and Zymomonas mobilis

Abstract: SUMMARYZymomonas anaerobia and 2. mobilis, grown on glucose + peptone + yeastextract medium, degraded no endocellular carbohydrate, DNA and protein even in prolonged starvation. No significant qualitative changes in protein content during starvation were detected by disc gel electrophoresis of crude extracts. Both organisms had a high content of RNA (22 % w/w) which was degraded on starvation. In 2. anaerobia RNA decreased linearly to 5 % of the dry weight in 125 hr. With 2. mobilis, half the RNA was degraded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1972
1972
1986
1986

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…4, this is associated with lower levels of biomass formation in the Zymomonas fermentation, rather than greater overall rates of ethanol formation and glucose con- Previous kinetic studies with various strains of Z.mobilis have been largely confined to glucose concentrations of less than 10g/l in complex media. (Bauchop and Elsden, 1960;Belaich and Senez, 1965;Forrest,1967;Dawes and Large, 1970;Belaich et al, 1972). …”
Section: Resultsmentioning
confidence: 92%
“…4, this is associated with lower levels of biomass formation in the Zymomonas fermentation, rather than greater overall rates of ethanol formation and glucose con- Previous kinetic studies with various strains of Z.mobilis have been largely confined to glucose concentrations of less than 10g/l in complex media. (Bauchop and Elsden, 1960;Belaich and Senez, 1965;Forrest,1967;Dawes and Large, 1970;Belaich et al, 1972). …”
Section: Resultsmentioning
confidence: 92%
“…Franzen & Binkley (1961) with E. coli and Smith & Maalare (1964) with Salmonella typhimurium, in batch culture, reported the ATP pool size to be independent of growth rate. Damoglou & Dawes (1967) reported that for E. coli grown in continuous culture the ATP pool remained constant, independent of growth rate, but gave no details, whereas in Zymomonas anaerobia the ATP pool increased during batch growth (Dawes & Large, 1970). Harrison & Maitra (1969) found that the ATP pool size in Klebsiella aerogenes growing in continuous culture limited by glucose, with oxygen in excess, remained constant at growth rates from 0.1 h-l to 0.5 h-l, when the culture was washing out.…”
Section: Discussionmentioning
confidence: 99%
“…ATP in bacterial extracts was measured by the firefly luminescence method using a high-gain photomultiplier tube as described by Dawes & Large (1970) except that the output of the photomultiplier tube was measured by a Smith ' Servoscribe' linear chart recorder (Smith Industries Ltd, Wembley, Middlesex).…”
Section: Methodsmentioning
confidence: 99%